2005
DOI: 10.1152/ajpgi.00093.2004
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α stimulates gastric epithelial cell proliferation

Abstract: is a cytokine produced during gastric mucosal injury. We examined whether TNF-␣ could promote mucosal repair by stimulation of epithelial cell proliferation and explored further the underlying mechanisms in a rat gastric mucosal epithelial cell line (RGM-1). TNF-␣ treatment (1-10 ng/ml) for 12 or 24 h significantly increased cell proliferation but did not induce apoptosis in RGM-1 cells. TNF-␣ treatment significantly increased cytosolic phospholipase A2 and cyclooxygenase-2 (COX-2) protein expression and PGE2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 33 publications
1
17
1
Order By: Relevance
“…We dynamically observed the changes of apoptosis and proliferation of gastric mucosal cells at different times from 30 min to 6 h after gastric I/R injury, Histological study of the normal gastric mucosa revealed a few apoptotic cells in the superficial layer of gastric mucosa and proliferating cells only in the gastric glandular neck area. These patterns contrast with previous reports [43,44] , supporting the notion that cell renewal and apoptosis are two essential processes maintaining the homeostasis of normal gastric mucosa. The pattern of simultaneous change in gastric mucosal cellular apoptosis during reperfusion is similar to that of gastric I/R injury; i.e., the level of apoptosis also reached its peak at 1 h after reperfusion when the gastric mucosal injury was most serious, and then declined.…”
Section: Discussioncontrasting
confidence: 63%
“…We dynamically observed the changes of apoptosis and proliferation of gastric mucosal cells at different times from 30 min to 6 h after gastric I/R injury, Histological study of the normal gastric mucosa revealed a few apoptotic cells in the superficial layer of gastric mucosa and proliferating cells only in the gastric glandular neck area. These patterns contrast with previous reports [43,44] , supporting the notion that cell renewal and apoptosis are two essential processes maintaining the homeostasis of normal gastric mucosa. The pattern of simultaneous change in gastric mucosal cellular apoptosis during reperfusion is similar to that of gastric I/R injury; i.e., the level of apoptosis also reached its peak at 1 h after reperfusion when the gastric mucosal injury was most serious, and then declined.…”
Section: Discussioncontrasting
confidence: 63%
“…We therefore sought to provide anatomical evidence that cells within the gastric mucosa (potentially including ghrelin-expressing cells) express receptors for these cytokines. Both TNF-a and IL-6 have been shown to stimulate proliferation of cultured gastric epithelial cells, and they are thought to play a role in normal gastric repair as well as in tumorigenesis (Shirota et al 1990, Howlett et al 2005, Luo et al 2005, Giraud et al 2007). However, we were unable to detect a significant level of expression of the TNF-a receptor, leukemia inhibitory factor receptor (LIF-R), or the gp130 subunit common to the entire IL-6 class of cytokines in our in situ hybridization assays (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…11,23,24 OPN KD AGS and NCC-S1M cells showed decreased cell proliferation compared with shRNA control cells following exposure to IL-1β and TNF-α for 24 h (Figure 6a). In addition, compared with shRNA control cells, OPN KD AGS and S1M cells showed an attenuation of the increase in the mitogen-activated protein kinase (MAPK)-related molecule, phosphorylated Akt, and Erk following exposure to IL-1β and TNF-α treatment (Figures 6b-e).…”
Section: Opn Deficiency Inhibits the Proliferation Of Gastricmentioning
confidence: 99%